Brucellosis involving the aorta and iliac arteries: a systematic review of 130 cases - Li, Xiao; Li, Xiaoyu; Cheng, Zhihua (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Brucellosis, the most common bacterial zoonosis, poses a serious threat to public health in endemic regions. Cardiovascular complications of brucellosis, mostly pericarditis or endocarditis, are the leading cause of brucellosis-related death. Complications involving the aorta and iliac arteries are extremely rare but can be life threatening. Our objective was to identify and review all reported cases of aortic and iliac involvement in brucellosis to provide a deep, up-to-date understanding of the clinical characteristics and management of the disease.Methods: Online searches in PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and the Chinese Wanfang database were conducted to collect articles reporting cases of brucellosis with aortic and iliac artery involvement. All data in terms of patient demographics, diagnostic methods, clinical manifestations, and treatment regimens and outcomes were extracted and analyzed in this systematic review.Results: A total of 79 articles were identified, reporting a total of 130 cases of brucellosis with aortic and iliac artery involvement. Of the 130 cases, 110 (84.5%) were male and 100 (76.9%) were over 50 years old. The patients had an overall mortality rate of 12.3%. The abdominal aorta was most commonly involved, followed by the ascending aorta, iliac artery, and descending thoracic aorta.Arteriosclerosis, hypertension, and smoking were the most common comorbidities. There were 71 patients (54.6%) who presented with systemic symptoms of infection at the time of admission.Endovascular therapy was performed in 56 patients (43.1%), with an overall mortality rate of 3.6%.Open surgery was performed in 52 patients (40.0%), with an overall mortality rate of 15.4%.Conclusions: Aortic and iliac involvement in brucellosis is extremely rare but can be life threatening.Its occurrence appears to be associated with the male gender, an older age, arteriosclerosis, and smoking. Although the number of reported cases in developing countries has increased significantly in recent years, its incidence in these countries may still be underestimated. Early diagnosis and therapeutic intervention are critical in improving patient outcome. Endovascular therapy has become a preferred surgical treatment in recent years, and yet, its long-term complications wait to be assessed.